The effect of human resources management practices and organizational citizens / Siti Sara Salleh - Salleh, Siti Sara
Working environment is one of the important things that need to be considered. This research study has been conducted to examine the effect of human resources management practices and organizational citizenship behavior for environment. The independent variables that include in this research study are training and development, compensation and benefit and performance appraisal. By conducting this research study, the researcher can identify whether the independent variable that being used in this study related to organizational citizenship behavior for environment. The total 130 set of questionnaires have been prepared and distribute to the respondent. The respondent for this study is being select randomly in Kuala Lumpur area. The researcher using Statistical Procedure for Social Science (SPSS) version 25 are used to calculate the data from the questionnaire. The result is being stated in chapter 4 of this research.